The Public University in Postandemia: New Wine in Old Wineskin? - Baraona Cockerell, Miguel (2023)
What impact in the medium and long term will the Pandemic have over our contemporary Society?¿and how will public universities face the current and future challenges? The answers to these two questions imply, in our perspective, a process of pedagogical innovation and in the areas of research and academic production according to the specific mission of those university systems that do not function for profit but for the wellbeing of Society and for the benefit of national and regional Latin American interest. The Centro de Estudios Generales of the Universidad Nacional of Costa Rica for many years has been pursuing a line work in education, research, outreach, and academic production guided by the principles and purposes derived from humanist though and action in our times, and the development of interdisciplinary study of complex and hypercomplex systems following some of the epistemological notions proposed by Rolando García and Jean Piaget (1982, 2000, 2006) in series of seminal works. This brief essay will cover three main sections: 1. A basic diagnosis of the global pre and post pandemic; 2. The importance of both general situations (nonetheless, emphasizing the new phenomena of the post pandemic phase) for present work in all academic areas of public universities; 3. A sketch of new humanist and interdisciplinary guidelines to contribute to our academic activity in these turbulent times.